Clearing the tracks of the White Pass & Yukon Railroad after a snow storm, Alaska, March 17, 1899. - Hegg, Eric A., 1867-1948 (1899)
Caption on image: "Men shoveling snow at switch back White Pass and Yukon Route. Mar 17 '99." Original image in Hegg Album 2, page 38 Original photograph by Eric A. Hegg 667; copied by Webster and Stevens 197.A Klondike Gold Rush.